Antioxidant Activity, Phenol and Flavonoid Contents of Indonesian Propolis - SYAMSUDIN (Asian Journal of Chemistry, 2009)
In present work, a systematic study of the relative antioxidant activity of Indonesian propolis collected from different regions of Java have been reported. The total phenol varied from 136.2 ± 10.1 to 203.7 ± 9.8 mg g-1 in the extracts. Flavones and flavonols were determined using aluminium chloride and expressed as quercetine equivalent, while flavanones were determined using 2,4-dinitrophenylhydrazine and expressed as naringenin. Contents of flavones and flavonols were similar for most samples and ranged from 1.7-7.3 %. The content of flavanones in propolis samples varies from 1.2-5.9 %. 1,1-Diphenyl-2-picrylhydrazine (DPPH) radical scavenging effect of the extracts was determined spectrophotometrically. IC50 of the extracts and the standard compounds quercetine was 8.44, 130.35, 19.27, 91.03 and 2.58 μg mL-1.